Австрійська мала проза ХХ століття: феномен мультикультурності - Зимомря, І. (Питання літературознавства, 2009)
Зроблена спроба розкрити сутність феномена мультикультурності австрійської малої прози крізь призму художнього досвіду Карла Еміля Францоза. В українській науці ця парадигма досі залишається недостатньо висвітленою. Функціональність ознак феномена мультикультурності розкривається на прикладі повісті „Німий” – знакового тексту у творчості К.Е.Францоза. The article is devoted to the essence of the multicultural phenomenon in the Austrian short stories through the prism of the creative experience of Karl Emil Franzos. In Ukrainian humanitarian science this paradigm is very weak point. Functionality of this phenomenon we can see in the Franzos’ text “Der Stumme” (Dumb). The Austrian writer pictures in this work the life and manners of the races of Galicia.